2016
DOI: 10.1038/srep21674
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-based vaccine expressing Ebola virus glycoprotein protects nonhuman primates from Ebola virus infection

Abstract: Ebolaviruses pose significant public health problems due to their high lethality, unpredictable emergence, and localization to the poorest areas of the world. In addition to implementation of standard public health control procedures, a number of experimental human vaccines are being explored as a further means for outbreak control. Recombinant cytomegalovirus (CMV)-based vectors are a novel vaccine platform that have been shown to induce substantial levels of durable, but primarily T-cell-biased responses aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 57 publications
0
57
0
Order By: Relevance
“…In most cases, the choice of a vector may be based on considerations that lie outside model results, and the model results will then inform the possibilities and avenues for success. Consider cytomegalovirus (CMV), a vector currently being used in the development of transmissible vaccines targeting Ebola and Lassa fever (Marzi et al, ; Murphy et al, ; Tsuda et al, , ). CMV appears promising because of its high level of species specificity, and ability to readily reinfect previously infected hosts (Murphy et al, ), a property shown to be critically important here, and in a previous study (Basinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the choice of a vector may be based on considerations that lie outside model results, and the model results will then inform the possibilities and avenues for success. Consider cytomegalovirus (CMV), a vector currently being used in the development of transmissible vaccines targeting Ebola and Lassa fever (Marzi et al, ; Murphy et al, ; Tsuda et al, , ). CMV appears promising because of its high level of species specificity, and ability to readily reinfect previously infected hosts (Murphy et al, ), a property shown to be critically important here, and in a previous study (Basinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At 16 weeks after the initial vaccination, the animals were challenged with EBOV, resulting in 75% protection. These results indicate that RhCMV/EBOV-GP is effective in NHPs despite pre-existing immunity to the vaccine vector, and survival of these animals appeared to correlate with total levels of EBOV GP-specific IgG, since the non-surviving animal showed the lowest antibody levels [67]. To further advance this candidate to clinical trials, the immunization regimens should be modified and tested to achieve optimum levels of protection first.…”
Section: Pre-clinical Testing Of Ebov Vaccines In Non-human Primatesmentioning
confidence: 99%
“…If a safe, efficient, and ethically accepted self‐spreading vaccine becomes available for use in great apes (as suggested by Marzi et al. ), relatively few individuals will require darting to induce high level of vaccination cover and longevity of protection in a population (Fig. a).…”
Section: Vaccinating Wild Great Apes Against Ebolamentioning
confidence: 99%
“…The vaccine candidates that are presently in human trials are considered to induce long-term protection sufficient to last for the duration of a human outbreak, but protection for months or even a couple of years might not be optimal for long-term prevention of EVD in wild apes (Stanley et al 2014, Wong et al 2014). If a safe, efficient, and ethically accepted self-spreading vaccine becomes available for use in great apes (as suggested by Marzi et al 2016), relatively few individuals will require darting to induce high level of vaccination cover and longevity of protection in a population (Fig. 2a).…”
Section: Prevention Of Ebola Spillover Into Habituated Populations Bymentioning
confidence: 99%